A Feasibility of Applying Phase Change Materials Derived from Polymer/VO2 Composites to Enhance Performance of PV Modules - Piwnuan, Chanakarn; Wootthikanokkhan, Jatuphorn; Kumnorkaew, Pisist; Kaewprajak, Anusit (Indochina Applied Sciences, 2025)
This study investigates the feasibility of using vanadium dioxide (VO2), a thermochromic and phase change material, to enhance the performance of photovoltaic (PV) modules. By coating a polymer film loaded with VO2 onto the modules, it was hypothesized that the module temperature can be reduced due to the endothermic latent heat associated with the phase transition of VO2. As a result, an improvement in power conversion efficiency (PCE) is expected. Firstly, VO2 particles were synthesized via a hydrothermal method and subsequently mixed with an acrylic binder at various concentrations (0.1-1.5 wt%) prior to film casting. Crystalline structure and morphology of the polymer composite films were characterized by X-ray diffraction and scanning electron microscopy techniques. Transition temperatures and optical properties of the composite films were determined by differential scanning calorimetry and UV/Vis spectroscopy. Heat shielding properties of the films were evaluated by monitoring temperature change inside a model house installed with the polymer composite films. The system exhibited remarkable temperature reduction with higher particle loading resulting in a more temperature drop. Additionally, the feasibility of applying these films to enhance the efficiency of PV modules was explored. Compared to reference PV modules without coating, the efficiency of the devices coated with polymer/VO2 film increased by approximately 1.74 %. The results were discussed in relation to phase transition, latent heat of VO2.